Cyrano de Bergerac - Rostand, Edmond, 1868-1918.; Untermeyer, Louis, 1885-1977. (Mineola, N.Y. : Dover Publications, 2000)
Contains the unabridged text of Edmond Rostand's play in which Cyrano, a swordsman with a very long nose, falls in love with the beautiful Roxanne and finds himself using his skill with words to help another man woo her.
Unabridged republication of the text of the Louis Untermeyer blank verse translation, originally published by the Heritage Press in 1954.
Translation of: Cyrano de Bergerac.
Adult
Adult
Keywords: Cyrano de Bergerac, -- 1619-1655 -- Drama; Cyrano de Bergerac, -- 1619-1655 -- Drama